Drivers to Participation in SHGs and Changes in Household Livelihood Constructs: A Longitudinal Survey in Nyakach Sub-County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2022)
Poverty reduction and socio-economic challenges since 1990s attracted institutions named Self-Help Groups (SHGs) among communities. Literature abound linking SHGs with empowerment especially of women albeit with weak methodology and failure to measure changes in livelihood participation. Poverty level still increased in areas like Nyakach Sub-County where SHGs operate. Poverty level increased from 18% to 43% until 2019, representing 238% rise. The study purposed to establish how participation in SHGs changed constructs of household livelihoods in Nyakach Sub-County, Kenya. The study hypotheses tested; absence of significant difference in household food security before and after joining SHGs, absence of significant difference in household healthcare access before and after joining SHGs, and absence of significant difference in household social capabilities before and after joining SHGs. Using Symbolic Interactionism Theory a longitudinal survey design was applied on 9450 target population. A sample of 384 provided data at two points before joining SHGs and after joining. Mean values of the two periods were compared using z-statistics. Findings showed that through participation in SHGs, improvement in food security (M=3.60; SD=1.39) and improvement in social capabilities (M=3.53; SD=1.36) were highly changed. Improvement in healthcare access was slight (M=2.73 ; SD=1.04). A significant and positive improvement in livelihood constructs of the SHG members was observed thus rejection of the null hypotheses (H01 ; H02 and H03). Conclusively, participation in SHGs had significant potential of improving livelihood constructs of households. It is recommended that healthcare as a construct of livelihood should be institutionalised through SHGs for more community reach.